Growth Of Zno Nanorods On Wire Via Sonochemistry Method For Glucose Sensing - Rayathulhan, Ruzaina (2017)
There has been much research on growth of ZnO nanorods on vanous substrates, and various growth methods. Sonochemical method is a well-known method for growing nanorods. Metal wire is a suitable substrate for the growth of ZnO nanorods as it can then be used as sensor electrode for sensing application. However there has not been any report on growth of ZnO nanorods on metal wire directly using sonochemical method. ZnO nanorods were directly grown on four different wires (silver (Ag), nickel (Ni), copper (Cu), and tungsten (W)) through sonochemical method and the best sample was chosen as electrode and tested for glucose sensing. Zinc nitrate hexahydrate and hexamethylenetetramine (HMT) were used as precursors for the growth of ZnO nanorods. The optimum condition for the growth of ZnO nanorods were determined by varying precursor molarity, sonication time and molar ratio of precursor solution.